DUA BURSA, SATU SAHAM: PENGARUH KURS RUPIAH DAN LIKUIDITAS PADA ARBITRASE TELKOM IDX DAN ADR - Yohanes Vianney Ario Nugroho; Nawwaf Raihan Ryant Mahendra; Desy Dwi Ariyani (Universitas Dian Nuswantoro, 2026)
This study analyzes the relationship between the Rupiah exchange rate, trading liquidity, and cross-market stock arbitrage, using PT Telekomunikasi Indonesia (Persero) Tbk listed on the Indonesia Stock Exchange (IDX) and as American Depositary Receipts (ADR) on the New York Stock Exchange (NYSE). Monthly data from January 2023 to December 2025 are analyzed using multiple linear regression. The results show that the Rupiah exchange rate has a negative and significant effect on arbitrage opportunities, indicating that fluctuations in the exchange rate tend to reduce potential gains from cross-market price differences. Trading liquidity also has a negative and significant effect, suggesting that higher liquidity accelerates price adjustments across markets. Simultaneously, both variables significantly influence cross-market stock arbitrage.